(untitled) (Journal of the College of Basic Education, 2022)
The research included an introduction to the research, an introduction to the research and its importance, in which the researcher dealt with the importance of research on the use of hypoxic exercises in terms of the concentration of lactic acid in the blood to develop speed endurance and the completion of a 200-meter run.